Dynamics of the COVID-19 Clinical Findings and the Serologic Response - Niavarani, Ahmadreza; Poustchi, Hossein; Shayanrad, Amaneh; Sharafkhah, Maryam; Mohammadi, Zahra; Mansour-Ghanaei, Fariborz; Joukar, Farahnaz; Roshandel, Gholamreza; Hormati, Ahmad; Ghadimi, Reza; Sadeghniiat-haghighi, Khosro; Abdollahi, Alireza; et al. (Frontiers in Microbiology, 2021)
The factors affecting the dynamics of lengthening of symptoms and serologic responses are not well known. In order to see how the serologic responses change in relation to the clinical features, we selected a group of 472 adults with a positive IgM/IgG antibody test result from a baseline study of the anti-SARS-CoV-2 seropositivity, assessed their COVID-19 and past medical histories, and followed them up in about three months. Nearly one-fourth of the subjects were asymptomatic at the baseline; 12.8% subjects became symptomatic at the follow-up when 39.8% of the subjects had some persisting symptoms. At the baseline, 6.1% showed anti-SARS-CoV-2 IgM positive, 59.3% only for IgG, and 34.5% for both. At the follow-up, these figures declined to 0.6%, 54.0%, and 4.4%, respectively, with the mean IgM and IgG levels declining about 6.3 and 2.5 folds. Blood group A was consistently linked to both sustaining and flipping of the gastrointestinal and respiratory symptoms. The baseline IgM level was associated with gastrointestinal symptoms and pre-existing cirrhosis in multivariate models. Both of the baseline and follow-up IgG levels were strongly associated with age, male, and lung involvement seen in chest computed tomography (CT)-scan. Finally, as compared with antibody decayers, IgM sustainers were found to be more anosmic (mean difference [MD]: 11.5%; P = 0.047) with lower BMI (MD: 1.30 kg/m2; P = 0.002), while IgG sustainers were more commonly females (MD: 19.2%; P = 0.042) with shorter diarrhea duration in the follow-up (MD: 2.8 days; P = 0.027). Our findings indicate how the anti-SARS-CoV-2 serologic response and COVID-19 clinical presentations change in relation to each other and basic characteristics.